PATH ANALYSIS OF RECORDING SYSTEM INNOVATION FACTORS AFFECTING ADOPTION OF GOAT FARMERS - Okkyla, S.; Dwijatmiko, S.; Kurnianto, E. (Diponegoro University, 2014)
The objective of this study was to evaluate the path analysis of recording system innovation factorsaffecting adoption of goat farmers. This study was conducted from January to February 2014 inPringapus District, Semarang Regency by using survey method. For determining the location, this studyused purposive sampling method. The amount of respondents were determined by quota samplingmethod. Total respondents randomly chosed were 146 farmers. The data were descriptively andquantitatively analyzed by using path analysis of statistical package for the social science (SPSS) 16.Independent variables in this study were internal factor, motivation, innovation characteristics,information source, and dependent variable was adoption. Analysis of linear regression showed thatthere was no significant effect of internal factor on adoption, so that it was important to use the trimmingmethod in path analysis. The result of path analysis showed that the influence of motivation, innovationcharacteristics and information source on adoption were 0.168; 0.720 and 0.09, respectively. Innovationcharacteristics were the greatest effect on adoption. In conclusion, by improving innovationcharacteristics of respondent through motivation and information source may significantly increase theadoption of recording system in goat farmers.